2016
DOI: 10.3892/ijo.2016.3458
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between angiotensin II and relaxin 2 in the progress of growth and spread of prostate cancer cells

Abstract: Abstract. Deregulation of locally secreted hormones, such as angiotensin II (Ang II) and relaxin 2 (RLN2), has been linked to a higher risk of select cancers or a poor prognosis in patients. In this study, for the first time a common effect of Ang II and RLN2 in relation to various aspects of prostate cancer development and metastasis are presented. Four independent colorimetric assays were used to analyze cell viability and proliferation. The changes of cell adhesion to extracellular matrix proteins and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Ang II can be detected easily in atherosclerotic plaques due to its high level of expression [Hoshida et al, 2001], which can impair the function and accelerate the senescence of EPCs [Zhou et al, 2010]. This is distinct from the growth-promoting effect of Ang II in many types of cancer cells [Dominska et al, 2016;Nowakowska et al, 2016]. Although the diminished effects of Ang II on the migration, adhesion, and tube formation of EPCs can be restored by natural extracts [Parzonko et al, 2013], they are not easily administered.…”
mentioning
confidence: 99%
“…Ang II can be detected easily in atherosclerotic plaques due to its high level of expression [Hoshida et al, 2001], which can impair the function and accelerate the senescence of EPCs [Zhou et al, 2010]. This is distinct from the growth-promoting effect of Ang II in many types of cancer cells [Dominska et al, 2016;Nowakowska et al, 2016]. Although the diminished effects of Ang II on the migration, adhesion, and tube formation of EPCs can be restored by natural extracts [Parzonko et al, 2013], they are not easily administered.…”
mentioning
confidence: 99%
“…Other researchers have also reported modulation of cell adhesion to the ECM by angiotensins. We observed previously that AngII improved ability of prostate cancer cells to adhere to the ECM 13 . Many other studies have demonstrated that Ang1–7 has an antagonistic effects than Ang II.…”
Section: Discussionmentioning
confidence: 74%
“…Our results clearly show that Ang1–7 can inhibit the anchorage-independent growth and non-adherent colony formation of both LNCaP and DU-145 cells, but not PC3. In contrast, Ang II was earlier observed to have a statistically insignificant stimulatory effect in all tested prostate cancer cells 13 .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations